Immunoproteomic identification of antigenic candidate Campylobacter jejuni and human peripheral nerve proteins involved in Guillain-Barré syndrome - Loshaj-Shala, Aida; Colzani, Mara; Brezovska, Katerina; Poceva Panovska, Ana; Suturkova, Ljubica; Beretta, Giangiacomo (Elsevier BV, 2018)
Immunoproteomics is become a potent methodology used for identifying immunoreactive proteins. In this study, an immunoproteomic approach based on 2-dimensional gel electrophoresis (2D-PAGE) and immunoblotting combined with high resolution mass spectrometry (MS) was used to identify immunoreactive proteins that might be involved in mechanisms of Guillain-Barré syndrome (GBS) development, regardless of their potential reciprocal molecular mimicry. Proteins isolated from C. jejuni and human peripheral nerve tissue (HPN) were separated with 2D SDS-PAGE and subjected to western blotting using serum samples from GBS patients. The peptides generated after proteolysis of the immunoreactive proteins were submitted to nanoflow-high performance liquid chromatography-nano electrospray ionization coupled to high resolution mass spectrometry (nHPLC-nESI-MS and MS/MS) followed by SEQUESTdata analysis for proteins identification. In C. jejuni, immunoreactivity was found for GroEL and DnaK, structural proteins (MOMP), key enzymatic proteins necessary for the microbial proliferation (adenylate kinase, enolase, inorganic pyrophosphatase and aspartate ammonia-lyase), and antioxidant enzymes (alkyl hydroperoxide reductase-AhpC and DNA protection during starvation protein - DNA protection factor against Fe2+-mediated oxidative stress). HPN immunoreactive proteins identified were heat shock proteins (HSP), intermediate filaments (vimentin and desmin), and other proteins and enzymes such as troponin/tropomyosin complex and ATP synthase subunit beta and the keratan sulfate proteoglycan lumican. The targeting of vimentin and desmin, suggested that the neuronal autoimmune damage is specifically directed to intermediate neuronal (vimentin) and neuromuscular IF, probably localized nearby cell surface, affording increased accessibility to autoantibodies. These findings suggest that the post-infectious development of GBS may be also associated to additional concomitant immune factors that lead to nerve damage generated by auto-immune trigger(s) different from molecular mimicry.